Strategi Pemasaran Untuk Meningkatkan Penjualan Produk Rak Sepatu Gantung Menggunakan Metode SWOT Dan QSPM Pada CV. Fafa Mandiri - Roberta Heni Anggit Tanisri; Mahfud Fauzan (JIE Scientific Journal on Research and Application of Industrial System, 2022)
CV. Fafa Mandiri is a small and medium-sized business of making and selling hanging shoe racks located in Aren Jaya Village, Bekasi City. The Number of companies engaged in the sale of hanging shoe racks that continue to emerge, forcing the company to continue to innovate in order to maintain its business. In addition to continuing to maintain good quality, management strives to increase sales of its products from the marketing side. This research was conducted to provide a new business strategy for CV. Fafa Mandiri on the sale of hanging shoe racks. Tha anlysis was carried out using the SWOT Method, (Strength, Weakness, Opportunity, Threat) and the QSPM (Quantitative Strategic Planning Matrix) method. The results of data processing and data analysis in this research process produced three alternative marketing strategies where the top priority is to increase cooperation with parties who are already known in this field to gain more trust from consumers so as to increase sales of this hanging shoe rack.